Wolbachia surface protein induces innate immune responses in mosquito cells - Pinto, S; Mariconti, M; Bazzocchi, C; Bandi, C; Sinkins, S (2012)
Background: Wolbachia endosymbiotic bacteria are capable of inducing chronic upregulation of insect immune genes in some situations and this phenotype may influence the transmission of important insect-borne pathogens. However the molecules involved in these interactions have not been characterized. Results: Here we show that recombinant Wolbachia Surface Protein (WSP) stimulates increased transcription of immune genes in mosquito cells derived from the mosquito Anopheles gambiae, which is naturally uninfected with Wolbachia; at least two of the upregulated genes, TEP1 and APL1, are known to be important in Plasmodium killing in this species. When cells from Aedes albopictus, which is naturally Wolbachia-infected, were challenged with WSP lower levels of upregulation were observed than for the An. gambiae cells. Conclusions: We have found that WSP is a strong immune elicitor in a naturally Wolbachia-uninfected mosquito species (Anopheles gambiae) while a milder elicitor in a naturally-infected species (Aedes albopictus). Since the WSP of a mosquito non-native (nematode) Wolbachia strain was used, these data suggest that there is a generalized tolerance to WSP in Ae. albopictus. © 2012 Pinto et al; licensee BioMed Central Ltd.